Patterns of pharmacotherapies used to treat alcohol use disorders: A population-based administrative data study - Nickel, Nathan; Leong, Christine; Prior, Heather; Konrad, Geoffrey; Bolton, James; MacWilliam, Leonard; Ekuma, Okechukwu; Paille, Michael; Valdivia, Jeff (International Journal of Population Data Science, 2018)
Introduction Alcohol use disorders (AUDs) – mental and/or physical health diagnoses due to harmful alcohol consumption – are associated with compromised quality of life for the individual. Over the past two decades, pharmacotherapies have been developed to treat alcohol addiction and may help mitigate the harmful outcomes linked with excessive alcohol. Objectives and Approach The objectives were to examine the pharmacotherapy dispensation patterns among individuals with an AUD and their mental health comorbidities. We used ICD codes from medical claims and hospital discharge data to identify anyone with a physical / mental health diagnosis due to harmful alcohol consumption – AUD, April 1, 1996-March 31, 2015. We identified mental health comorbidities using administrative health records. Drug dispensation data were used to identify all first-time prescriptions for acamprosate, naltrexone, or disulfiram occurring after an initial AUD diagnosis. Generalized linear models tested for predictors of receiving a prescription and to identify differences in mental health comorbidities. Results We identified 53,556 treatment niave individuals with an AUD who were eligible to receive one of these three prescriptions. 493 of these received a prescription for acamprosate, naltrexone, or disulfiram. The majority of prescriptions came from general practitioners from urban centers. Those with a prescription were significantly more likely to have a comorbid mood or anxiety diagnosis. Those with a prescription were more likely to have a physician visit for a mental health issue a year to two years before diagnosis compared with those who did not have a prescription; and, they were more likely to be dispensed a selective serotonin, a sedative, and an anti-anxiety medication prior to receiving an AUD diagnosis. Conclusion/Implications Drug therapies to aid in the recovery from AUD are being underutilized. Diagnosis of and treatment for mental health disorders is more common among those dispensed these medications. Programs that study clinicians’ use of AUD-targeted drug therapies should be considered, while psychiatric services in addiction care require significant improvement.